ESC expert statement on the effects on mood of the natural cycle and progestin-only contraceptives. (4th July 2017) - Merki-Feld, G. S.; Apter, D.; Bartfai, G.; Grandi, G.; Haldre, K.; Lech, M.; Lertxundi, R.; Lete, I.; Lobo Abascal, P.; Raine, S.; Roumen, F.; Serfaty, D.; et al.
Abstract: Hormonal fluctuations during the natural cycle, as well as progestins used for hormonal contraception, can exert effects on mood especially in vulnerable women. Negative effects of levonorgestrel-releasing intrauterine contraception on mood are rare.